Temporal variation in the vertical stratification of blubber fatty acids alters diet predictions for lactating Weddell seals - Wheatley, KE; Nichols, PD; Hindell, MA; Harcourt, RG; Bradshaw, CJA (Journal of Experimental Marine Biology and Ecology, 2007)
Fatty acid signature analysis of blubber has been used to study the foraging ecology of some marine mammals. However, species-specific information on fatty acid (FA) deposition, distribution and mobilization is required to develop further the application of FA as trophic markers within the marine environment. Blubber samples were collected from adult female Weddell seals post-parturition and end of lactation, and were divided into inner and outer half sections. We determined the degree to which there was vertical stratification in FA composition, and how this changed over the lactation period. Inner and outer layers of post-parturition blubber cores separated into two distinct groups. Sixty-two per cent of the dissimilarity between the two layers was accounted for by a higher abundance of monounsaturated fatty acids (18:19c and 16:17c) in the outer blubber layer, and more saturated fatty acids (16:0 and 14:0) in the inner layer. By end of lactation, the FA composition of the inner layer was different to post-parturition samples, and 20:53 had the highest fractional mobilization of all FA. In contrast, the proportion of FA in the outer layer did not change, and there was more variability in the fractional mobilization of FA indicating mobilization was not uniform across the blubber layer. Dietary predictions changed considerably when highly mobilized FA were removed from analyses, and predictions were more consistent with previous dietary studies. The lack of uniformity in FA mobilization adds problems to the future use of FASA in dietary predictions, highlighting the need for more detailed information on FA mobilization. 2007 Elsevier B.V. All rights reserved.